PENSION GUARANTEE PROTECTION FOR ATHLETES BASED ON STATUTORY REGULATIONS IN INDONESIA - Yustyana, Shafira Putri; Sinayangsih, Gina Gaharuli; NurCahyani, Alvia Ragita; Purnomo, Carissa Akhlaq Mulia (Indonesian Journal of Sports Law, 2024)
Athlete is a sportsperson who takes part in sports training and championships regularly, systematically, integrated, tiered and continuously to achieve achievements. It is appropriate for the government to pay attention to athletes who have struggled hard in taking part in the championship by paying attention to the welfare of the athletes, especially for athletes who are no longer part of the club or national team. Law Number 11 of 2022 concerning sports is the legal basis regarding the government's role and responsibilities towards sportsmen in Indonesia. The research method used in writing this law is normative juridical. The research results show that the existence of Law Number 11 of 2022 concerning Sports has not been able to guarantee the welfare and old age security for former athletes, even though in they contributed many achievements for Indonesia. In fact, quite a few athletes after entering retirement still have to struggle hard to survive by working in old age. Thus, there is a need for legal certainty that regulates old age security for athletes in both active and passive era of their contribution in sports